A macro theory with micro foundations - Sweeney, Richard J. (Cincinnati : South-Western Publishing, Co., 1974)
This book tries to help reconcile micro and macroeconomics.
Chapter 1 Introduction -- Chapter 2 The Microeconomic Model of Firm Behavior -- Chapter 3 A Simple Macro Model with Excess Capacity -- Chapter 4 A Simple Macro Model with Positive Excess Aggregate Demand for Output -- Chapter 5 Labor Supply, the Level of Employment, and the Rate of Unemployment -- Chapter 6 Macroeconomic Policy Implications of the Model -- Chapter 7 The Model with Wealth Effects and a Business Demand for Money -- Chapter 8 A Two-Sector Versions of the Simple Macro Model.
Includes bibliographical references and index.
Keywords: MACROECONOMICS -- MATHEMATICAL MODELS